Risk Factors and Prognosis for Metastatic Follicular Thyroid Cancer - Wu, Ming-Hsien; Lee, Yi-Yin; Lu, Yu-Ling; Lin, Shu-Fu (Frontiers in Endocrinology, 2022)
Background: Follicular thyroid cancer (FTC) is the second most common malignancy of thyroid. About 7%–23% of patients with FTC have distant metastasis. The aim of this study was to investigate the risk factors associated with distant metastasis and the impact of distant metastasis on survival in FTC patients. Methods: Patients with FTC were analyzed using a prospectively maintained dataset of thyroid cancer registered at a tertiary hospital in Taiwan between December 1976 and May 2020. Results: A total of 190 patients with a mean follow-up of 7.7 years were included in this study, including 29 with distant metastasis at diagnosis, 14 who developed metastasis during follow-up, and 147 without metastasis. Multivariate analysis adjusted for age, gender, tumor stage, and extrathyroidal invasion revealed old age (≥ 55 years) (adjusted odds ratio, 27.6; 95% confidence interval [CI], 8.75–86.8; P < 0.001) and extrathyroidal invasion (odds ratio, 24.1; 95% CI, 3.50–166.5; P = 0.001) were significantly associated with an increased risk of distant metastasis. Metastasis was correlated with higher cancer-specific mortality (adjusted hazard ratio, 35.5; 95% CI, 6.1–206.1; P < 0.001). In addition, patients with metastatic FTC diagnosed on initial presentation had the lowest 10-year cancer-specific survival rate (26.0%), followed by those who developed metastatic disease after initial treatment (76.6%), while patients without metastasis were all alive (100%) (P ≤ 0.002 for all comparisons). Conclusions: Age and extrathyroidal invasion are significant risk factors for distant metastasis of FTC. Patients with metastatic FTC, especially when diagnosed on initial presentation, have dismal survival outcomes.